EFL CLASSROOM BEHAVIOURS AND INTERACTIONS: A CASE STUDY OF A TEACHER AND HER STUDENTS IN A STATE JUNIOR HIGH SCHOOLIN ACADEMIC YEAR 2019/2020 IN THE CITY OF KUPANG, EAST NUSA TENGGARA - Melkysedes Bali Ate; Clemens Kolo; Laurensius Kian Bera (Academic Journal of Educational Sciences, 2021)
This research aims at describing teacher’s behaviours, students’ behaviours and the interactions which are performed by teacher and students in the classroom. To achieve the aims, the researcher used a case study method, which is qualitative, focusing on Junior High School (JHS) teacher and students, who use English as a foreign language (EFL), in Kupang City, East Nusa Tenggara Province (NTT), Indonesia. The instrument technique to get the data was participant observation. It was conducted from January to March 2020. The data were analyzed descriptively. It was found that: 1) teacher behaviours including ‘gaining students’ attention’ and ‘giving reinforcement’ are very good and expected to be maintained; others, including ‘motivating students’, ‘managing classroom’, and ‘providing follow up action’ are not really good and expected to be improved; and others including ‘informing learning procedures’, ‘evaluating’, ‘making references’, and ‘reviewing the newly learned material’, are bad and strongly expected to be improved; 2) students behaviours including ‘paying attention to teacher’ and ‘responding teacher’s reward’ are very good and expected to be maintained; others including ‘getting motivated’, ‘participating in classroom management’, and attending to follow up activity’ are not really good and expected to be improved; and others including ‘knowinglearning procedures’, ‘participating in review of material’, ‘demonstrating learning achievement in learning assessment’, and ‘making references’, are bad and strongly expected to be improved; 3) teacher and students mostly performed teacher-oriented interactions which can be seen in activities of ‘asking and answering questions’ and ‘providing patterns of interaction’. It is really recommended for teacher and students to be able to demonstrate those behaviours in the classroom. Behaviours that serve as high class of appearance started from 80% to 100% are very good and expected to be maintained because their capacity quality of supporting learning are high.